Microstructures in pyrope garnets from Thailand - Phichaikamjornwut,B. (Chiang Mai University, 2015)
Garnets associated with ruby-sapphire that are related to basaltic and gabbroic rocks from Trat, Chanthaburi and Si Sa Ket Provinces in eastern and northeastern parts of Thailand have been observed. All crystals are orangey red to brownish red colored, refractive index of 1.75-1.77, specific gravity of 3.498-3.789, and sizes between 0.3-1.5 cm in diameter. The physical properties and chemical compositions are comparable to those reported for the pyrope end-member: Py59-68Al18-26Gr11-13 for basalts-related pyrope and Py52-57Al27-31Gr13-14 for gabbros-related pyrope. Garnets associated with ruby-sapphire contained several types of inclusions and microstructures. Inclusions are composed of needles, black inclusions, cloud, minute exsolved particles, liquid inclusions and tension discs. Several kinds of microstructural features can be recognized under microscopic examination, including: (1) a high density of fiber-like tubes penetrating from rims to cores of grains, (2) a network of tubes that looks like a bird's nest, and (3) a thread-like line along grain-boundary microcracks of garnet crystals. The chemical analyses of the materials within tubes reveal the clay mineral composition and was formed during alteration processes after garnet host. Kink-bands of a densely formed fibers-like tubes imply that they are the result of the deformation processes. This discovery of the microstructural features in pyrope garnets are unique and are first reported for Thai garnets.